INTERLANGUAGE IN THE TRANSLATION OF SEVENTH SEMESTER STUDENTS OF STUDY PROGRAM OF ENGLISH UNIVERSITAS BRAWIJAYA - HAKIKI, M. AMINULLAH (Jurnal Ilmiah Mahasiswa FIB, 2014)
Hakiki, Muhammad Aminullah. 2014.  Interlanguage in the Translation of Seventh Semester Students of Study Program of English Universitas Brawijaya. Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies, University of Brawijaya. Supervisor: Fatimah; Co-supervisor: Yana Shanti Manipuspika.  Keywords: Error, interlanguage, translation, interference error, intralingual error.  Language is used in human communication, either in  spoken or written one. Language as a source of communication has a vital role in human life. As people communicate with other people with different languages, it is not enough only to learn one’s native language. To strive in this globalization era, a person needs to learn foreign languages and master the skills especially translation. The more languages one can master, the more he is able  to compete. One of the  foreign languages that should be learned is English as it is one of the languages that is used in communication around the world. In  this research, the researcher investigates the kinds of errors and most frequent  errors produced by seventh semester students in their translation. The researcher used qualitative research and content analysis in order to answer the research problems. In analyzing the data, the researcher used the theory of sources of errors by Richards (1971) and Lott (1983). The data were five translations made by seventh semester students who have taken “Introduction to Translation” class with a grade of A. In data collection, the researcher provided the participants a test in which they have to translate from Bahasa Indonesia to English within 45 minutes. This study found that the most frequent error is false concept hypothesized with 59 errors (68.7%), followed by incomplete application of rules with 17 errors (19.4%), then interlingual with 7 errors (7.6%), and transfer of structure with 4 errors (4.3%). The researcher found that there are still many translation errors made by the students even though they have high grades in the translation class. The researcher suggests the next researchers who want to conduct a similar study by using another theory and giving the participants a  different criteria, like the TOEFL score.